The Relevance of Hans‐Georg Gadamer's Concept of Tradition to the Philosophy of Education. Issue 5 (October 2015) - Leiviskä, Anniina
ABSTRACT In this article, Anniina Leiviskä argues that the educational relevance of Hans‐Georg Gadamer's concept of tradition has remained unacknowledged because of the conservatism that has been associated with Gadamer's hermeneutics, particularly his notion of tradition. Therefore, Leiviskä seeks to reveal the reflective, nonconservative nature of Gadamer's concept of tradition in order to illuminate its significance with respect to the philosophy of education. Utilizing Gadamer's reinterpretation of the Aristotelian notion of phronesis, she outlines a concept of situated rationality that rests upon the idea of the historicity of human existence, and she suggests that this concept may be used to define a central aim of education. Leiviskä argues that instead of disengaged objectivity, rationality as phronesis stands for the reflective reappropriation of one's tradition, which is enabled by one's situatedness in history and requires encountering other horizons — including the horizons of the past — through which one may be addressed and challenged.